Genome sequence and description of Desnuesiella massiliensis gen. nov., sp. nov. a new member of family Clostridiaceae. (May 2016) - Hadjadj, L.; Tidjani Alou, M.; Sokhna, C.; Lagier, J.-C.; Raoult, D.; Rolain, J.-M.
Abstract: Desnuesiella massiliensis, strain MT10 T gen. nov., sp. nov. is a newly proposed genus within the family Clostridiaceae, isolated from the digestive microbiota of a child suffering from kwashiorkor. Desnuesiella massiliensis is a facultatively anaerobic, Gram-positive rod. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 5 503 196-bp long genome (one chromosome but no plasmid) contains 5227 protein-coding and 81 RNA genes, including 14 rRNA genes.